Estudo comparativo entre os recptores hormonais esteroidicos (estrogeno e progesterona) e o grau de elastose no carcinoma mamario ductal invasor - Almeida, Francisco Manuelito Lima de (1984)
Positivity of steroid receptors (e4íA.ogen and pfLOge-Síe-tone) and levei were investigated in a series of 41 tumors of patients with breast carcinoma of correlated with me.nAtsiu.aZ AtataA, hZAtoZogZc dZ^eA.eníZaXZon, epéí/ieZZzzZ c.e.ZZuZaA.ZZí/, nucZea/i atypy, and Zymphocytz Zn^ZZtftatZon. Correlation between ER and PR positivity and the presence of elastose (ZeveZ-5 1 and 2] occurred in 0) cases there was no ER-po-óZZZue. However, total correlation with poAtttve ER and for half of the case with po-óZ-tZve PR. In the present study we observed greater occurrence of positive elastose in tumors with a low levei of histologic differentiation, epithelial cellularity, nuclear atypy, and lymphocyte infiltration. The incidence and concentration of estrogen receptors (ER) were higher among post-menopausal women. No variation in progesterone receptors (PR) by menstrual status was observed. The highest distribution of positive ER and PR was detected in tumors having AZZyht and modeaate. nuclear atypy, and lymphocyte infiltration.